IMPLEMENTATION OF QABDH REQUIREMENTS IN MURABAHA FINANCING AT KOPERASI SYIRKAH BERKAH BERSAMA (KSBB) SIDOARJO - Endro Wibowo (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
One of the financing procedures that are not by Sharia principles in Murabaha financing is the practice of selling goods by an Islamic Financing Institution before they are owned to financing customers. Seeing this phenomenon, Koperasi Syirkah Berkah Bersama (KSBB) took the initiative to become a Sharia financial institution capable of serving its members through Murabaha financing by really paying attention to Sharia compliance, especially from the aspect of implementing handover or qabdh in Murabaha financing. The purpose of this study is to find out how the implementation of handover or qabdh in Murabaha financing and the analysis of sharia compliance with this implementation at KSBB Sidoarjo. The research method used in this study is qualitative research with a case study approach. The data analysis technique used is descriptive-qualitative analysis. The research data comes from interviews with several informants and documents related to Murabaha financing at KSBB. The data that has been obtained is analyzed and compared with related theories. The results of this research indicate that in the process of Murabaha financing at KSBB, the management of KSBB does not represent members in purchasing the goods submitted to suppliers. KSBB also ensures that the goods are fully controlled before being sold to members who apply for financing. The entire Murabaha financing process at KSBB, especially from the qabdh aspect, does not violate sharia compliance set by the DSN MUI.